Development of a database and E-wallet system for GPS expressway tolling system - Nur Afifah, Akbar (2022)
Toll roads have provided the majority of highway network funding. By constructing a toll road, it is possible to offer a variety of enhanced services to road users, all of which can be calculated to ensure that they achieve the desired results. The major stakeholders in the toll road field, are responsible for developing the toll project and providing operational services using associated technology thus achieving the primary goal of constructing a toll, which is to satisfy customers. Every day, the toll in the city center and industrial area is expected to see a large amount of traffic consisting of a range of vehicles ranging from personal vehicles to light and heavy commercial vehicles, multi-axle trucks, and so on. In addition, traffic problems are also critical during the holiday season, especially during festive seasons. Even the fact that new highways are still being built in Malaysia still can't change much and the gradual rise in traffic volume can no longer be met solely by the construction of new highways. Develop a GPS expressway tolling system capable of replacing the current tolling system by reducing the number of human resources working at toll stations and utilizing GPS tracking of all vehicles entering and exiting the toll. To make it easier for end-users, encourage the use of e-wallets in tolling systems. A voiding traffic jams at toll booths allows for smooth driving without having to worry about paying the toll. Furthermore, from the start in chapter one explains the introduction of the GPS Expressway Tolling system and the background reason why the project is focusing on overcoming the current tolling system. To make it easier for end users, encourage the usage of e-wallets in tolling systems. You can drive without worrying about paying the toll by avoiding traffic congestion at toll booths. This study, emphasizes the difference with other tolling systems and how the GPS Tolling system is different and able to overcome many problems that the previous Tolling system wasn't able to settle the score with. Finally, and certainly not least, the main overview of the SDP Project itself (GPS Expressway Tolling System) and how it runs and functions with more in-depth emphasis on how it works and what it's able to accomplish in the long run.